2019
DOI: 10.1007/s13318-019-00555-x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Enzymatic and Nonenzymatic Conjugation of Treosulfan with Glutathione

Abstract: Background and ObjectivesTreosulfan (dihydroxybusulfan), licensed for the treatment of ovarian carcinoma, is investigated in clinical trials as a myeloablative agent for conditioning prior to hematopoietic stem cell transplantation. Clinical experience shows that treosulfan exhibits lower organ toxicity than busulfan, including hepatotoxicity. Elimination of busulfan primarily via enzymatic conjugation with glutathione (GSH) in the liver is considered to be the main cause of the drug’s hepatotoxicity and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…These can occur spontaneously, proceed with the participation of small-molecule compounds or be light-induced. As has been reported for several compounds (i.e., isothiocyanates or catecholamines), the reactive GSH thiol-group, which possesses strong nucleophilic properties, provides the redox potential also for non-enzymatic conjugation [ 10 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These can occur spontaneously, proceed with the participation of small-molecule compounds or be light-induced. As has been reported for several compounds (i.e., isothiocyanates or catecholamines), the reactive GSH thiol-group, which possesses strong nucleophilic properties, provides the redox potential also for non-enzymatic conjugation [ 10 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…A significant route of drug detoxification in many species is the conjugation of xenobiotic with reduced tripeptide glutathione (GSH; L- γ -glutamyl-L-cysteinyl-glycine) [ 8 ]. Due to the high nucleophilic reactivity of the GSH thiol group, this process can be non-enzymatic and/or mediated by various GSH-dependent enzymes [ 9 , 10 ]. On the other hand, depending on the properties of the substrate, GSH conjugation may also play an important role in bioactivation reactions as it can generate toxic conjugates [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with GSTA1*B are poor metabolizers of busulfan, thereby exhibiting high systemic busulfan exposure, leading to organ toxicities and adverse HCT outcomes 40–43 . Romański et al 44 . performed a kinetic analysis to examine treosulfan–GSH conjugation in vitro and showed that treosulfan does not undergo spontaneous or GST‐mediated conjugation with GSH.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with GSTA1*B are poor metabolizers of busulfan, thereby exhibiting high systemic busulfan exposure, leading to organ toxicities and adverse HCT outcomes. [40][41][42][43] Romański et al 44 performed a kinetic analysis to examine treosulfan-GSH conjugation in vitro and showed that treosulfan does not undergo spontaneous or GST-mediated conjugation with GSH. We screened for GSTA1*B haplotype, which was shown to explain variability in busulfan PK in the present study, and assessed the effect of the genotype on treosulfan/S, S-EBDM exposure.…”
Section: Discussionmentioning
confidence: 99%